Anti-inflammatory effects of montelukast on smoke-induced lung injury in rats - ERCAN, FERİHA; ŞİRVANCI, SERAP (NOVAMEDIA, 2010)
Aim: To evaluate the effects of montelukast in smoke-induced lung injury. Methods: 28 Wistar-Albino rats were enrolled into 4 groups with 7 rats per group. The healthy control group was exposed to fresh air while all rats in the 3 experimental groups were exposed to cigarette smoke for 20 weeks for 2 hours per day. After histopathological verification of smoke induced lung injury, montelukast (0.1 mg/kg) dissolved in Na(2)CO(3) was given in one group (MON), Na(2)CO(3) only was given in another group (MON control) and placebo was injected in the third group (COPD control) intraperitoneally for 21 days. At the end of this period blood samples were obtained for serum TNF-alpha assessment and light and electron microscopy analyses were performed on the lung tissues of sacrificed rats. Results: Serum TNF-a levels in the MON group were significantly lower than in the MON control and COPD control groups (38.84 +/- 4.9 pg/ml, 77.5 +/- 5.8 pg/ml and 79.2 +/- 6.9 pg/ml respectively, p < 0.05). Furthermore there was no statistically significant difference between the MON group and healthy controls with respect to serum TNF-alpha levels (38.84 +/- 4.9 pg/ml vs. 29.5 +/- 3.6 pg/ml, p > 0.05). Light and electron microscopic evaluation of the lungs demonstrated that the total histopathological damage score of the lung samples was significantly lower in the MON group than in MON controls and COPD controls (5.14 +/- 0.5, 8.4 +/- 0.6 and 8.7 +/- 0.4 respectively, p < 0.05), while there was no significant difference between the MON group and healthy controls (5.1 +/- 0.6 vs 2.3 +/- 0.2, p > 0.05). Conclusion: These findings suggest that montelukast might have a protective effect on smoke-induced lung injury in rats both from a histopathological and inflammatory point of view.
Keywords: Chronic bronchitis; inflammation; montelukast; smoking; OBSTRUCTIVE PULMONARY-DISEASE; KAPPA-B ACTIVATION; SEVERE COPD; ASTHMA; MODERATE; INFLAMMATION; MARKERS